7-cysteine-pyrrole conjugate: A new potential DNA reactive metabolite of pyrrolizidine alkaloids. (2nd January 2016) - He, Xiaobo; Xia, Qingsu; Ma, Liang; Fu, Peter P.
ABSTRACT: Pyrrolizidine alkaloids (PAs) require metabolic activation to exert cytotoxicity, genotoxicity, and tumorigenicity. We previously reported that (±)-6, 7-dihydro-7-hydroxy-1-hydroxymethyl-5H-pyrrolizine (DHP)-derived DNA adducts are responsible for PA-induced liver tumor formation in rats. In this study, we determined that metabolism of riddelliine and monocrotaline by human or rat liver microsomes produced 7-cysteine-DHP and DHP. The metabolism of 7-glutathionyl-DHP by human and rat liver microsomes also generated 7-cysteine-DHP. Further, reaction of 7-cysteine-DHP with calf thymus DNA in aqueous solution yielded the described DHP-derived DNA adducts. This study represents the first report that 7-cysteine-DHP is a new PA metabolite that can lead to DNA adduct formation.